2013
DOI: 10.1021/ol4006079
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(II)-Catalyzed Regioselective Reductive Coupling of α-Imino Esters with Dienes

Abstract: A method for the highly regioselective reductive coupling reaction of N-aryl-α-imino esters with dienes is described. The method utilizes the RuHCl(CO)(PPh3)3/iPrOH catalytic system under an Ar atmosphere and provides α-branched allylic α-amino acid derivatives. Application of this transformation to the concise synthesis of a natural plant growth regulator is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 47 publications
(18 reference statements)
0
25
0
Order By: Relevance
“…In contrast, the development of corresponding late transition metal catalyzed amine C-H functionalizations has proven challenging. [92][93][94] Indeed, with the exception of the present authors work, [95][96][97][98][99] all other late transition metal catalyzed hydroaminoalkylations require pyridyl directing groups in combination with mono-olefin reactants. [100][101][102][103][104][105][106][107][108] In a significant departure from prior art, it was found that ruthenium catalyzed hydrogen transfer from 4-aminobutanol to 1-substituted-1,3-dienes results in the generation of dihydropyrrole-allylruthenium pairs, which combine to form products of hydroaminoalkylation with good to complete control of anti-diastereoselectivity (Scheme 18).…”
Section: Hydroaminoalkylationmentioning
confidence: 60%
See 2 more Smart Citations
“…In contrast, the development of corresponding late transition metal catalyzed amine C-H functionalizations has proven challenging. [92][93][94] Indeed, with the exception of the present authors work, [95][96][97][98][99] all other late transition metal catalyzed hydroaminoalkylations require pyridyl directing groups in combination with mono-olefin reactants. [100][101][102][103][104][105][106][107][108] In a significant departure from prior art, it was found that ruthenium catalyzed hydrogen transfer from 4-aminobutanol to 1-substituted-1,3-dienes results in the generation of dihydropyrrole-allylruthenium pairs, which combine to form products of hydroaminoalkylation with good to complete control of anti-diastereoselectivity (Scheme 18).…”
Section: Hydroaminoalkylationmentioning
confidence: 60%
“…In contrast, 2-propanol-mediated reductive couplings of allenes or dienes with formaldimines (generated in situ from saturated 1,3,5-triazines) are efficient and selective processes. [95][96][97][98] Specifically, ruthenium catalyzed transfer hydrogenation of allenes in the presence of 1,3,5-tris(4-methoxyphenyl)-hexahydro-1,3,5-triazine provides products of hydroaminomethylation as single regioisomers. 96 Under similar conditions, butadiene and related 2-substituted dienes engage in regioselective reductive C-C coupling to furnish products of hydroaminomethylation.…”
Section: Hydroaminoalkylationmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] A mixture of ethyl glyoxylate (20.4 mg, 0.20 mmol), substituted amine (0.20 mmol) and anhydrous sodium sulfate (1.0 mmol) in 2 mL of toluene was stirred for 0.5 hour at room temperature. The mixture was then filtered and the solvent was removed under reduced pressure to produce the corresponding a-imino esters.…”
Section: Procedures For the Preparation Of A-imino Estersmentioning
confidence: 99%
“…a-Imino ester (1j) were prepared using the previously reported procedure. [25] All the alkenes substrates are commercially available. These are not the final page numbers!…”
mentioning
confidence: 99%